The Problem of the Choice of Revascularization in Combined Lesion of the Coronary and Carotid Arteries. Review of Current Recommendations and Article Series - A. N. Kazantsev; R. A. Vinogradov; A. A. Erofeev; V. N. Kravchuk; A. S. Zharova; А. A. Sorokin; D. V. Shmatov; G. Sh. Bagdavadze; A. V. Korotkikh (Неотложная медицинская помощь, 2022)
This article provides data from the current Russian (National guidelines for the management of patients with diseases of the brachiocephalic arteries of 2013; Recommendations “Blockage and stenosis of the carotid artery” of the Ministry of Health of the Russian Federation, 2016) and foreign (European Society of Cardiology / European Society of Vascular Surgeons for Diagnosis and Treatment Peripheral Artery Diseases 2017; Recommendations for myocardial revascularization of the European Society of Cardiology and the European Association of Cardio-Thoracic Surgeons 2018) recommendations regarding the choice of a revascularization strategy for combined coronary and carotid artery disease. Conclusions are drawn about the unresolved issue. A literature review of the largest series of Russian articles by one institution devoted to this topic was carried out. Hospital and long-term outcomes have been demonstrated, as well as predictors of complications for various revascularization strategies. The stages of creation and the results of approbation of a new computer program for risk stratiﬁ cation, which makes it possible to determine the mathematical probability of the development of unfavorable cardiovascular events during the implementation of various surgical tactics, taking into account the individual characteristics of the patient. A conclusion was made about the effectiveness of this development.